Strategies of Flexible Integration and Enlargement of the European Union: a Club-theoretical and Constitutional Economics Perspective - Clara Brandi; Michael Wohlgemuth (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2006)
Our paper proceeds as follows: As a point of departure, part two highlights the heterogeneity among EU member states following the recent enlargement, while part three reviews three main alternative conceptions of flexible integration as they were discussed in political circles. Part four applies Buchanan's and Tullock's Calculus of Consent (1962) to the tension between deepening and widening the EU. Part five introduces basic elements of the economic theory of clubs, analyzes the notion of the EU as a club and examines flexible integration in a club-theoretical framework. Part six considers several alternative integration models in view of the conclusions of both club theory and constitutional economics, while part seven focuses more specifically on a club-of-clubs approach that we tend to favour as an ideal-type model for a European Union of the future. Part eight evaluates the relative weaknesses and strengths of flexible integration according to the club-of-clubs approach and part nine advocates some further institutional recommendations before part ten concludes.
Keywords: 330